2011
DOI: 10.1093/jxb/err174
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the Arabidopsis SEC24A in male transmission

Abstract: Eukaryotic cells use COPII-coated carriers for endoplasmic reticulum (ER)-to-Golgi protein transport. Selective cargo capture into ER-derived carriers is largely driven by the SEC24 component of the COPII coat. The Arabidopsis genome encodes three AtSEC24 genes with overlapping expression profiles but it is yet to be established whether the AtSEC24 proteins have overlapping roles in plant growth and development. Taking advantage of Arabidopsis thaliana as a model plant system for studying gene function in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Because Atsec24A null mutant is lethal, and the aberrant morphology of the ER and the Golgi caused by the point mutation in AtSEC24A cannot be suppressed by overexpression of AtSEC24B or AtSEC24C, these isoforms might be functionally different (Faso et al, 2009;Nakano et al, 2009). A further study showed that the loss of AtSEC24A function induces a defect in pollen germination but does not affect the female gametophyte (Conger et al, 2011). On the other hand, AtSEC24B and AtSEC24C were shown to function redundantly in both male and female gametogenesis (Tanaka et al, 2013).…”
Section: Cargo Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Atsec24A null mutant is lethal, and the aberrant morphology of the ER and the Golgi caused by the point mutation in AtSEC24A cannot be suppressed by overexpression of AtSEC24B or AtSEC24C, these isoforms might be functionally different (Faso et al, 2009;Nakano et al, 2009). A further study showed that the loss of AtSEC24A function induces a defect in pollen germination but does not affect the female gametophyte (Conger et al, 2011). On the other hand, AtSEC24B and AtSEC24C were shown to function redundantly in both male and female gametogenesis (Tanaka et al, 2013).…”
Section: Cargo Sortingmentioning
confidence: 99%
“…On the other hand, AtSEC24B and AtSEC24C were shown to function redundantly in both male and female gametogenesis (Tanaka et al, 2013). Moreover, microarray analysis of microspores indicates that the AtSEC24A expression peak comes earlier than that of AtSEC24B during pollen development (Conger et al, 2011). Since Arabidopsis SEC24 proteins are also thought to function in cargo sorting like the homologs in yeast, the difference between AtSEC24A and AtSEC24B/C may reflect specific cargo recognition.…”
Section: Cargo Sortingmentioning
confidence: 99%
“…In humans, alterations in ER-mediated processes cause disease phenotypes that have been classified into three groups: (1) cargo retention and degradation, (2) cargo accumulation and ER stress, and (3) ER transport machinery diseases (Aridor and Hannan, 2000). Also in plant cells, defects in ER functionality lead to various developmental defects (Tamura et al, 2005;Conger et al, 2011;Stefano et al, 2012;Renna et al, 2013), supporting a critical role of the ER for organism biology at large.…”
mentioning
confidence: 95%
“…Through positional cloning, we determined that the mutation occurs in the SEC24A gene, which encodes the cargo-binding subunit of the COPII vesicle complex. In addition to altered cell size, this unique sec24a-2 allele shows pleiotropic defects, including dwarfism, which have not been reported previously for other SEC24A alleles (Faso et al, 2009;Nakano et al, 2009;Conger et al, 2011). Although the mutant is developmentally aberrant, both cytokinesis and auxin response appear normal in sec24a-2, unlike other transport mutants.…”
mentioning
confidence: 56%
“…Yeast and mammalian studies have shown that residue 693 is crucial for cargo binding (Miller et al, 2003;Mancias and Goldberg, 2007). In a later study, Conger et al (2011) found that a transfer DNA insertion allele, sec24a-1, leads to a male transmission defect in heterozygous mutants, and thus no homozygous individuals can be recovered (Fig. 1F).…”
Section: A Unique Sec24a Allele Increases Cell Size In the Sepal Epidmentioning
confidence: 90%